Effectiveness of Sociodrama Techniques to Increase Students' Religious Tolerance SMAN 1 Margahayu - Muhammad Rezza Septian; Mamat Supriatna; Juntika Nurihsan; Nandang Budiman; Williya Novianti (Universitas PGRI Yogyakarta, 2024)
The attitude of religious tolerance needs to be instilled and improved early on in students who are in school. This research aims to test the effectiveness of sociodrama technique that can empirically increase religious tolerance in class X students of SMA Negeri 1 Margahayu. This research uses a quantitative approach. The method used in this research is quasi experiment with non-equivalent pretest-postest control group design. Data collection using religious tolerance instruments. Data analysis used non-parametric statistics. The participants in this study were students of class X-IA 5 SMA Negeri 1 Margahayu, totalling 34 people. Sampling in this study used random sampling technique. The results showed that the Sociodrama technique was empirically proven to be effective in increasing religious tolerance with an Asymp. Sig (2 tailed) of 0.030 is smaller than α. 0.05. The conclusion is that the sociodrama technique is empirically proven to be effective in increasing students' religious tolerance. Keywords: sociodrama, religious tolerance, student